2020
DOI: 10.1111/dme.14292
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to completing oral glucose tolerance testing in women at risk of gestational diabetes

Abstract: Aim Complications of gestational diabetes (GDM) can be mitigated if the diagnosis is recognized. However, some atrisk women do not complete antenatal diagnostic oral glucose tolerance testing (OGTT). We aimed to understand reasons contributing to non-completion, particularly to identify modifiable factors. Methods Some 1906 women attending a tertiary UK obstetrics centre (2018-2019) were invited for OGTT based on risk-factor assessment. Demographic information, test results and reasons for non-completion were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 30 publications
2
52
0
5
Order By: Relevance
“…This was pertinent during the pandemic peak, when having all women attend during a small, timeframe was logistically difficult, and challenging for women without private transport. More data are required to better understand whether the requirement for an overnight fast and early‐morning attendance influences uptake of the OGTT, especially among socially disadvantaged women in real‐world clinical settings 6 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This was pertinent during the pandemic peak, when having all women attend during a small, timeframe was logistically difficult, and challenging for women without private transport. More data are required to better understand whether the requirement for an overnight fast and early‐morning attendance influences uptake of the OGTT, especially among socially disadvantaged women in real‐world clinical settings 6 …”
Section: Discussionmentioning
confidence: 99%
“…10 Although some women may refuse OGTT testing, it is clear that screening for GDM is not consistently implemented in accordance with guideline recommendations. 6,10 A recent case-control study identified a 44% greater risk of stillbirth in women with risk factors when an OGTT was not performed. 9 Likewise, women with raised fasting plasma glucose (FPG) levels who were not diagnosed with GDM experienced a fourfold greater risk of stillbirth.…”
Section: What's New?mentioning
confidence: 99%
See 3 more Smart Citations